Resistin Enhances Inflammatory Cytokine Production in Coronary Artery Tissues by Activating the NF-κB Signaling. (9th October 2016) - Gao, Fang; Si, Feifei; Feng, Siqi; Yi, Qijian; Liu, Ruixi
Abstract : Purpose. Kawasaki disease (KD) is a systemic vasculitis and is a leading cause of coronary artery lesions (CALs) in childhood. Our previous study has shown higher levels of serum Resistin in KD patients with coronary aneurysm. This study aimed at examining the association of Resistin with inflammatory cytokine expression in mouse model of coronary arteritis and determining the potential mechanisms. Methods. C57BL/6 mice were injected with Lactobacillus cell wall extract (LCWE) to induce coronary arteritis. The relative levels of Resistin, TNF- α, IL-1 β, and MMP-9 expression and inflammatory infiltrates in the coronary arteries were determined longitudinally by quantitative RT-PCR, ELISA, and histology. The effect of TLR4 and NF- κ B activation on Resistin-induced TNF- α and IL-1 β expression in human coronary artery endothelium cells (HCAECs) was examined by quantitative RT-PCR. Results. Higher levels of Resistin, TNF- α, IL-1 β, and MMP-9 expression were associated with the degrees of inflammatory infiltrates in the coronary artery walls of the LCWE-injected mice. Resistin enhanced TNF- α and IL-1 β expression in HCAECs at 18 or 24 hours after stimulation. Pretreatment with anti-TLR4 attenuated Resistin-enhanced IL-1 β, but not TNF- α, expression and pretreatment with parthenolide or QNZ demolished Resistin-enhanced TNF- α expression in HACECs. Pretreatment with parthenolide, but not QNZ, blocked Resistin-enhanced IL-1 β expression in HCAECs. Conclusion. Resistin may enhance inflammation by cross-talking with TLR4/NF- κ B signaling during the development of coronary arteritis in mice.